Thermoelectric conversion materials, thermoelectric conversion elements, and sulfides
Patent Information
- Application Number
- JP2019166589
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-15
- Filing Date
- 2019-09-12
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2039-09-12
AI Technical Summary
【0020】 上記の熱電変換材料は、Cuと、Snと、Al、Zn、及びInの少なくとも1つと、を有する硫化物を含有しており、又は、Cuと、Snと、Al、Zn、In、及びGaの少なくとも1つと、を有する硫化物を含有しており、所望の熱電特性を有している。また、上記の硫化物は、熱電変換材料等のエネルギー変換のための材料として利用できる。
Smart Images

Figure 0007640223000003 
Figure 0007640223000004 
Figure 0007640223000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoelectric conversion material, a thermoelectric conversion element, and a sulfide. [Background technology]
[0002] In recent years, sulfides have been attracting particular attention as semiconductor materials such as thermoelectric conversion materials and solar cell materials. Solar cell materials are materials that absorb light such as ultraviolet light, visible light, or infrared light, and convert light energy into electrical energy through the photovoltaic effect. Materials containing silicon or gallium arsenide have been put to practical use as solar cell materials. Meanwhile, in recent years, there has been active research into the application of sulfide materials such as copper-indium-selenium sulfide (CIS) or copper-zinc-tin sulfide (CZTS) to solar cell materials. In addition, Non-Patent Documents 1 and 2 each describe Cu 3 AlSnS 5 and Cu 3 InSnS 5 The synthesis method of nanoparticles is described, and the authors are considering their application to solar cells and are measuring the ultraviolet-visible-near infrared absorption spectra and current-voltage curves of these materials.
[0003] A thermoelectric conversion material is a material that generates a voltage due to the temperature difference between both ends of the material by the Seebeck effect, converts thermal energy into electrical energy, or generates a temperature difference by electrical energy by the Peltier effect. In recent years, sulfides containing copper and other metals have been attracting attention as thermoelectric conversion materials. For example, Non-Patent Documents 3 and 4 each describe Cu sulfides having a corrucite structure. 26 V 2 M 6 S 32 (M=Ge, Sn) and Cu with corrucite structure 26 V 2 M 6 S 32In addition, Patent Document 1 describes a thermoelectric conversion material made of a composite metal sulfide having a specific crystal structure and containing copper and at least one metal other than copper that is a first transition element or a p-block element as a main component. In addition, Non-Patent Document 5 describes a thermoelectric conversion material made of Cu 2 SnS 3 Cu, with Cu or Sn partially replaced by Al. 5 AlSn 2 S 8 The thermoelectric properties of have been predicted by first-principles calculations.
[0004] In Non-Patent Document 6, Cu 2 Tl 2 SnS 4 It has been reported that the thermal conductivity of is 0.6 W / (m K) at 300 K. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-48730 A
[0006] [Non-Patent Document 1] ChemPlusChem, (Germany), 2015, Vol.80, 652-655 [Non-Patent Document 2] CrystEngComm,(Eng), 2013, Vol.15, p.10459-10463 [Non-Patent Document 3] Applied Physics Letters, (US), 2014, Vol.105, 132107 [Non-Patent Document 4] Journal of Applied Physics, (US), 2014, Vol.116, 063706 [Non-Patent Document 5] Journal of Electronic Materials, (US), 2016, Vol. 45, No.3, p. 1453-1458 [Non-Patent Document 6] Chemistry of Materials,(US), 2005, Vol.17, No. 11, p. 2875-2884 Summary of the Invention [Problem to be solved by the invention]
[0007] According to Patent Document 1 and Non-Patent Documents 3 to 6, no specific thermoelectric conversion material containing a sulfide having Cu, Sn, and at least one of Al, Zn, and In is described. In addition, Non-Patent Documents 1 and 2 do not describe a specific thermoelectric conversion material containing a sulfide having Cu, Sn, and at least one of Al, Zn, and In. 3 AlSnS 5 and Cu 3 InSnS 5 No measurement results regarding the thermoelectric properties are described.
[0008] In consideration of these circumstances, the present invention provides a thermoelectric conversion material containing a sulfide of a specific composition having Cu, Sn, and at least one of Al, Zn, and In. The present invention also provides a thermoelectric conversion material containing a sulfide of a specific composition having Cu, Sn, and at least one of Al, Zn, In, and Ga. The present invention also provides novel sulfides that can be used in energy conversion such as thermoelectric conversion and solar cells. [Means for solving the problem]
[0009] The present invention relates to Cu h-a M i-b Sn j-c D a+b+c S k The composition is represented by M is at least one element selected from Al, In, and Zn; D is a metal element other than Cu, Al, In, Zn, and Sn; a ≧ 0, b ≧ 0, c ≧ 0, 2.8 ≦ h ≦ 3.2, 0.8 ≦ i ≦ 1.2, and 0.8 ≦ j ≦ 1.2 are satisfied, and k is a value that maintains electrical neutrality, When M contains Zn, 0≦a+b+c≦0.2; If M does not contain Zn, then 0≦a+b+c≦0.5. A thermoelectric conversion material is provided.
[0010] The present invention also provides a method for producing a semiconductor device comprising the steps of: Cu h-a Al x-b1 In i-x-b2 Sn j-c Z a+b1+b2+c S k The composition is represented by Z is a metal element other than Cu, Al, In, and Sn; Contains sulfide, which satisfies 0≦x≦i, a≧0, b1≧0, b2≧0, c≧0, 0≦a+b1+b2+c≦0.5, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2, and k is a value that maintains electrical neutrality. A thermoelectric conversion material is provided.
[0011] The present invention also provides a method for producing a semiconductor device comprising the steps of: Cu h-a Al x-b3 Zinc i-x-b4 Sn j-c T a+b3+b4+c S k The composition is represented by T is a metallic element other than Cu, Al, Zn, and Sn; Contains sulfide, which satisfies 0≦x≦i, a≧0, b3≧0, b4≧0, c≧0, 0≦a+b3+b4+c≦0.2, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2, and k is a value that maintains electrical neutrality. A thermoelectric conversion material is provided.
[0012] The present invention also provides a method for producing a semiconductor device comprising the steps of: Cu h-a R i-b Sn j-c E a+b+c S k The composition is represented by R is at least one element selected from Al, In, Zn, and Ga; E is a metal element other than Cu, Al, In, Zn, Ga, and Sn; a ≧ 0, b ≧ 0, c ≧ 0, 2.8 ≦ h ≦ 3.2, 0.8 ≦ i ≦ 1.2, and 0.8 ≦ j ≦ 1.2 are satisfied, and k is a value that maintains electrical neutrality, When R contains Zn, 0≦a+b+c≦0.2; If R does not contain Zn, then 0≦a+b+c≦0.5. A thermoelectric conversion material is provided.
[0013] The present invention also provides a method for producing a semiconductor device comprising the steps of: Cu h-a Al x-b1 Ga i-x-b2 Sn j-c J a+b1+b2+c S k The composition is represented by J is a metal element other than Cu, Al, Ga, and Sn; Contains sulfide, which satisfies 0≦x≦i, a≧0, b1≧0, b2≧0, c≧0, 0≦a+b1+b2+c≦0.5, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2, and k is a value that maintains electrical neutrality. A thermoelectric conversion material is provided.
[0014] The present invention also provides a method for producing a semiconductor device comprising the steps of: A thermoelectric conversion element including the above thermoelectric conversion material is provided.
[0015] The present invention also provides a method for producing a semiconductor device comprising the steps of: Cu h-a M i-b Sn j-c D a+b+c S k The composition is represented by M is at least one element selected from Al, In, and Zn, and contains Zn; D is a metal element other than Cu, Al, In, Zn, and Sn; a ≧ 0, b ≧ 0, c ≧ 0, 0≦a+b+c≦0.2, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2 are satisfied, and k is a value that maintains electrical neutrality, Provide sulfides.
[0016] The present invention also provides a method for producing a semiconductor device comprising the steps of: Cu h-a Al x-b1 In i-x-b2 Sn j-c Z a+b1+b2+c S k The composition is represented by Z is a metal element other than Cu, Al, In, and Sn; Provided is a sulfide that satisfies 0≦x≦i, a≧0, b1≧0, b2≧0, c≧0, 0≦a+b1+b2+c≦0.5, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2, and k is a value that maintains electrical neutrality.
[0017] The present invention also provides a method for producing a semiconductor device comprising the steps of: Cu h-a Al x-b3 Zinc i-x-b4 Sn j-c T a+b3+b4+c S k The composition is represented by T is a metallic element other than Cu, Al, Zn, and Sn; Provided is a sulfide that satisfies 0≦x≦i, a≧0, b3≧0, b4≧0, c≧0, 0≦a+b3+b4+c≦0.2, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2, and k is a value that maintains electrical neutrality.
[0018] The present invention also provides a method for producing a semiconductor device comprising the steps of: Cu h-a R i-b Sn j-c E a+b+c S k The composition is represented by R is at least one element selected from Al, In, Zn, and Ga, and contains Ga; E is a metal element other than Cu, Al, In, Zn, Ga, and Sn; a ≧ 0, b ≧ 0, c ≧ 0, 2.8 ≦ h ≦ 3.2, 0.8 ≦ i ≦ 1.2, and 0.8 ≦ j ≦ 1.2 are satisfied, and k is a value that maintains electrical neutrality, When R contains Zn, 0≦a+b+c≦0.2; When R does not contain Zn, 0≦a+b+c≦0.5. Provide sulfides.
[0019] The present invention also provides a method for producing a semiconductor device comprising the steps of: Cu h-a Al x-b1 Ga i-x-b2 Sn j-c J a+b1+b2+c S k The composition is represented by J is a metal element other than Cu, Al, Ga, and Sn; Provided is a sulfide that satisfies 0≦x≦i, a≧0, b1≧0, b2≧0, c≧0, 0≦a+b1+b2+c≦0.5, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2, and k is a value that maintains electrical neutrality. Effect of the Invention
[0020] The above thermoelectric conversion material contains a sulfide having Cu, Sn, and at least one of Al, Zn, and In, or contains a sulfide having Cu, Sn, and at least one of Al, Zn, In, and Ga, and has desired thermoelectric properties. The above sulfide can be used as a material for energy conversion such as a thermoelectric conversion material. [Brief description of the drawings]
[0021] [Figure 1A] FIG. 1A is a cross-sectional view showing an example of a thermoelectric conversion element according to the present invention. [Figure 1B] FIG. 1B is a cross-sectional view showing another example of a thermoelectric conversion element according to the present invention. [Figure 2A] FIG. 2A is a graph showing the X-ray diffraction pattern of the powder of Example 1. [Figure 2B] FIG. 2B is a graph showing the X-ray diffraction pattern of the powder of Example 2. [Figure 2C] FIG. 2C is a graph showing the X-ray diffraction pattern of the powder of Example 3. [Figure 2D]FIG. 2D is a graph showing the X-ray diffraction pattern of the powder of Example 4. [Figure 2E] FIG. 2E is a graph showing the X-ray diffraction pattern of the powder of Example 5. [Figure 2F] FIG. 2F is a graph showing the X-ray diffraction pattern of the powder of Example 6. [Figure 2G] FIG. 2G is a graph showing the X-ray diffraction pattern of the powder of Example 7. [Figure 2H] FIG. 2H is a graph showing the X-ray diffraction pattern of the powder of Example 8. [Figure 2I] FIG. 2I is a graph showing the X-ray diffraction pattern of the powder of Example 9. [Figure 2J] FIG. 2J is a graph showing the X-ray diffraction pattern of the powder of Example 10. [Figure 3A] FIG. 3A is a graph showing the X-ray diffraction pattern of the sample according to Example 1. [Figure 3B] FIG. 3B is a graph showing the X-ray diffraction pattern of the sample according to Example 2. [Figure 3C] FIG. 3C is a graph showing the X-ray diffraction pattern of the sample according to Example 3. [Figure 3D] FIG. 3D is a graph showing the X-ray diffraction pattern of the sample according to Example 4. [Figure 3E] FIG. 3E is a graph showing the X-ray diffraction pattern of the sample according to Example 5. [Figure 3F] FIG. 3F is a graph showing the X-ray diffraction pattern of the sample according to Example 6. [Figure 3G] FIG. 3G is a graph showing the X-ray diffraction pattern of the sample according to Example 7. [Figure 3H] FIG. 3H is a graph showing the X-ray diffraction pattern of the sample of Example 8. [Figure 4A] FIG. 4A is a graph showing the temperature change in thermal conductivity of the sample according to Example 1. [Figure 4B] FIG. 4B is a graph showing the temperature change in thermal conductivity of the sample according to Example 2. [Figure 4C] FIG. 4C is a graph showing the temperature change in thermal conductivity of the sample according to Example 3. [Figure 4D] FIG. 4D is a graph showing the temperature change in thermal conductivity of the sample according to Example 4. [Figure 4E] FIG. 4E is a graph showing the temperature change in thermal conductivity of the sample according to Example 5. [Figure 4F] FIG. 4F is a graph showing the temperature change in thermal conductivity of the sample according to Example 6. [Figure 4G] FIG. 4G is a graph showing the temperature change in thermal conductivity of the sample according to Example 7. [Figure 4H] FIG. 4H is a graph showing the change in thermal conductivity of the sample according to Example 8 with respect to temperature. [Figure 5A] FIG. 5A is a graph showing the temperature changes in electrical conductivity and electrical resistivity of the sample according to Example 1. [Figure 5B] FIG. 5B is a graph showing the temperature changes in electrical conductivity and electrical resistivity of the sample according to Example 2. [Figure 5C] FIG. 5C is a graph showing the change in electrical conductivity with temperature of the sample according to Example 3. [Figure 5D] FIG. 5D is a graph showing the temperature change in electrical conductivity of the sample according to Example 4. [Figure 5E] FIG. 5E is a graph showing the change in electrical conductivity with temperature of the sample according to Example 5. [Figure 5F] FIG. 5F is a graph showing the change in electrical conductivity with temperature of the sample according to Example 6. [Figure 5G] FIG. 5G is a graph showing the change in electrical conductivity with temperature of the sample according to Example 7. [Figure 5H] FIG. 5H is a graph showing the change in electrical conductivity with temperature of the sample according to Example 8. [Figure 6A] FIG. 6A is a graph showing the temperature change of the Seebeck coefficient and the power factor of the sample according to Example 1. [Figure 6B]FIG. 6B is a graph showing the temperature change of the Seebeck coefficient and the power factor of the sample according to Example 2. [Figure 6C] FIG. 6C is a graph showing the temperature change of the Seebeck coefficient and the power factor of the sample according to Example 3. [Figure 6D] FIG. 6D is a graph showing the temperature change of the Seebeck coefficient and the power factor of the sample according to Example 4. [Figure 6E] FIG. 6E is a graph showing the temperature change of the Seebeck coefficient and the power factor of the sample according to Example 5. [Figure 6F] FIG. 6F is a graph showing the temperature change of the Seebeck coefficient and the power factor of the sample according to Example 6. [Figure 6G] FIG. 6G is a graph showing the temperature change of the Seebeck coefficient and the power factor of the sample according to Example 7. [Figure 6H] FIG. 6H is a graph showing the temperature change of the Seebeck coefficient and the power factor of the sample according to Example 8. [Figure 7A] FIG. 7A is a graph showing the dimensionless figure of merit of the sample according to Example 1. [Figure 7B] FIG. 7B is a graph showing the dimensionless figure of merit of the sample according to Example 2. [Figure 7C] FIG. 7C is a graph showing the dimensionless figure of merit of the sample according to Example 3. [Figure 7D] FIG. 7D is a graph showing the dimensionless figure of merit of the sample according to Example 4. [Figure 7E] FIG. 7E is a graph showing the dimensionless figure of merit of the sample according to Example 5. [Figure 7F] FIG. 7F is a graph showing the dimensionless figure of merit of the sample according to Example 6. [Figure 7G] FIG. 7G is a graph showing the dimensionless figure of merit of the sample according to Example 7. [Figure 7H] FIG. 7H is a graph showing the dimensionless figure of merit of the sample according to Example 8. [Figure 8A] FIG. 8A is a transmission electron microscope (TEM) photograph of the powder according to Example 1. [Figure 8B] FIG. 8B is a TEM photograph of the powder according to Example 3. [Figure 8C] FIG. 8C is a TEM photograph of the powder according to Example 4. [Figure 8D] FIG. 8D is a TEM photograph of the powder according to Example 5. [Figure 8E] FIG. 8E is a TEM photograph of the powder according to Example 6. [Figure 8F] FIG. 8F is a TEM photograph of the powder according to Example 7. [Figure 8G] FIG. 8G is a TEM photograph of the powder according to Example 8. [Figure 8H] FIG. 8H is a TEM photograph of the powder of Example 9. [Figure 8I] FIG. 8I is a TEM photograph of the powder according to Example 10. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, embodiments of the present invention will be described. Note that the following description is merely an example of the present invention, and the present invention is not limited to these.
[0023] <Thermoelectric conversion materials> The thermoelectric conversion material according to the present invention is h-a M i-b Sn j-c D a+b+c S kThe present invention contains a sulfide having a composition represented by the formula: where M is at least one element selected from Al, In, and Zn. D is a metal element other than Cu, Al, In, Zn, and Sn. D may be one type of element or multiple types of elements. The sulfide satisfies a≧0, b≧0, c≧0, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2. In addition, k is a value that maintains the electrical neutrality of the sulfide. k is, for example, 5. Furthermore, when M contains Zn, 0≦a+b+c≦0.2, and when M does not contain Zn, 0≦a+b+c≦0.5. After much trial and error, the present inventors have newly discovered that a material containing a sulfide having such a composition exhibits desired thermoelectric properties.
[0024] In the sulfide, M may contain only one element selected from Al, In, and Zn, or may contain two or more elements selected from Al, In, and Zn.
[0025] M includes, for example, Zn. In this case, the band gap of the thermoelectric conversion material is narrowed, and it is expected that the thermoelectric conversion material will exhibit high thermoelectric performance in the low temperature region. In addition, it is believed that by adjusting the amount of Zn, the electron density at the band edge of the valence band is increased, and the Seebeck coefficient of the thermoelectric conversion material is likely to be increased.
[0026] In the sulfide, D is, for example, at least one selected from the group consisting of Mn, Fe, Co, and Ni. D may be Ga.
[0027] The sulfide is Cu h-a Al x-b1 In i-x-b2 Sn j-c A a+b1+b2+c S kHere, A is a metal element other than Cu, Al, In, and Sn. A may be one type of element or multiple types of elements. The sulfide satisfies 0≦x≦i, a≧0, b1≧0, b2≧0, c≧0, 0≦a+b1+b2+c≦0.5, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2. In addition, k is a value that maintains the electrical neutrality of the sulfide. k is, for example, 5.
[0028] For example, A is at least one element selected from the group consisting of Mn, Fe, Co, Ni, and Zn. A may be Ga.
[0029] The sulfide is Cu h-a Al x-b3 Zinc i-x-b4 Sn j-c Q a+b3+b4+c S k The composition may be represented by the formula: Q is a metal element other than Cu, Al, Zn, and Sn. 0≦x≦i, a≧0, b3≧0, b4≧0, c≧0, 0≦a+b3+b4+c≦0.2, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2 are satisfied. k is a value that maintains electrical neutrality. k is, for example, 5.
[0030] Q is, for example, at least one element selected from the group consisting of Mn, Fe, Co, and Ni. Q may be Ga.
[0031] The sulfide typically satisfies h+i+j=5.0. The sulfide, for example, satisfies h=3.0, i=1.0, and j=1.0. The sulfide is preferably Cu. 3 Al x In 1-x SnS 5 The composition is represented by the formula: where 0≦x≦1 is satisfied. The sulfide is Cu 3 AlSnS 5 or Cu 3 InSnS 5 The sulfide may have a composition represented by the formula:3 Al x Zinc 1-x SnS 5 In this case, the sulfide may have a composition represented by the formula: where 0≦x≦1 is satisfied. In this case, the sulfide may have a composition represented by the formula: 3 ZnSnS 5 The composition may be represented by the following formula:
[0032] From another viewpoint, the thermoelectric conversion material according to the present invention is h-a Al x-b1 In i-x-b2 Sn j-c Z a+b1+b2+c S k The material may contain a sulfide having a composition represented by the formula: Z is a metal element other than Cu, Al, In, and Sn. Z may be one type of element or multiple types of elements. The sulfide satisfies 0≦x≦i, a≧0, b1≧0, b2≧0, c≧0, 0≦a+b1+b2+c≦0.5, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2. In addition, k is a value that maintains the electrical neutrality of the sulfide. k is, for example, 5. After much trial and error, the present inventors have newly discovered that such a material also exhibits the desired thermoelectric properties.
[0033] Z is, for example, at least one element selected from the group consisting of Mn, Fe, Co, Ni, Zn, and Ga. The sulfide typically satisfies h+i+j=5.0. The sulfide typically satisfies h=3.0, i=1.0, and j=1.0.
[0034] From another viewpoint, the thermoelectric conversion material according to the present invention is h-a Al x-b3 Zinc i-x-b4 Sn j-c T a+b3+b4+c S kThe material may contain a sulfide having a composition represented by the formula: T is a metal element other than Cu, Al, Zn, and Sn. T may be one type of element or multiple types of elements. The sulfide satisfies 0≦x≦i, a≧0, b3≧0, b4≧0, c≧0, 0≦a+b3+b4+c≦0.2, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2. In addition, k is a value that maintains the electrical neutrality of the sulfide. k is, for example, 5. After much trial and error, the present inventors have newly discovered that such a material also exhibits the desired thermoelectric properties.
[0035] T is, for example, at least one element selected from the group consisting of Mn, Fe, Co, Ni, and Ga. The sulfide typically satisfies h+i+j=5.0. The sulfide typically satisfies h=3.0, i=1.0, and j=1.0.
[0036] From another viewpoint, the thermoelectric conversion material according to the present invention is h-a R i-b Sn j-c E a+b+c S k The material may contain a sulfide having a composition represented by the formula: R is at least one element selected from Al, In, Zn, and Ga. E is a metal element other than Cu, Al, In, Zn, Ga, and Sn. E may be one type of element or multiple types of elements. The sulfide satisfies a≧0, b≧0, c≧0, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2. In addition, k is a value that maintains the electrical neutrality of the sulfide. k is, for example, 5. Furthermore, when R contains Zn, 0≦a+b+c≦0.2, and when R does not contain Zn, 0≦a+b+c≦0.5. After much trial and error, the present inventors have newly discovered that such a material also exhibits the desired thermoelectric properties.
[0037] E is, for example, at least one element selected from the group consisting of Mn, Fe, Co, and Ni.
[0038] From another viewpoint, the thermoelectric conversion material according to the present invention is h-a Al x-b1 Ga i-x-b2 Sn j-c J a+b1+b2+c S k The material may contain a sulfide having a composition represented by the formula: J is a metal element other than Cu, Al, Ga, and Sn. J may be one type of element or multiple types of elements. The sulfide satisfies 0≦x≦i, a≧0, b1≧0, b2≧0, c≧0, 0≦a+b1+b2+c≦0.5, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2. In addition, k is a value that maintains the electrical neutrality of the sulfide. k is, for example, 5. After much trial and error, the inventors have newly discovered that such a material also exhibits the desired thermoelectric properties.
[0039] J is, for example, at least one element selected from the group consisting of Mn, Fe, Co, Ni, and Zn.
[0040] Cu h-a R i-b Sn j-c E a+b+c S k Sulfides having a composition represented by the formula h-a Al x-b1 Ga i-x-b2 Sn j-c J a+b1+b2+c S k The sulfide having a composition represented by the formula (I) typically satisfies h+i+j=5.0. The sulfide, for example, satisfies h=3.0, i=1.0, and j=1.0. The sulfide is preferably Cu 3 Al x Ga 1-x SnS 5 The composition is represented by the formula: where 0≦x≦1 is satisfied. The sulfide is Cu 3 GaSnS 5 The composition may be represented by the following formula:
[0041] The sulfide preferably has a crystal structure in which anions are mainly arranged tetrahedronally. Examples of the structure in which anions are arranged tetrahedronally include a zinc blende structure, a wurtzite structure, and an inverse fluorite structure. More preferably, the sulfide has at least one crystal structure of a zinc blende structure and a wurtzite structure. The zinc blende crystal structure is a structure in which a cubic close-packed lattice of anions is expanded, and half of the vacancies of the tetrahedrons consisting of anions are occupied by cations. Therefore, even if the cation sites are replaced by elements of different sizes in the zinc blende crystal structure, the remaining half of the vacancies not occupied by cations buffers the distortion of the structure. For this reason, it is considered that elements of a certain ratio or less can replace cations in the zinc blende crystal structure. In addition, the zinc blende structure is more likely to have a high electrical conductivity than sulfides having a thiospinel crystal structure composed of the same elements, and has advantageous properties as a thermoelectric conversion material. Examples of structures similar to the zinc blende structure include a corrucite structure, a germanite structure, a stannite structure, and a kesterite structure, etc. These structures also have anions arranged in a tetrahedral shape.
[0042] In the thermoelectric conversion material, the sulfide is, for example, sintered. This makes it easier for the sulfide to have desired properties as a thermoelectric conversion material. In addition, the thermoelectric conversion material can be molded into a predetermined shape, making it easy to handle the thermoelectric conversion material in the manufacture of a thermoelectric conversion element.
[0043] The thermoelectric conversion material has, for example, a lattice thermal conductivity of 1.3 W / (m·K) or less at 373 to 673K.
[0044] The dimensionless figure of merit ZT defined by the following formula (1) is known as an index of the performance of thermoelectric conversion materials. Here, S represents the Seebeck coefficient, σ represents the electrical conductivity, T represents the absolute temperature, and κ represents the thermal conductivity. As shown in formula (1), a low thermal conductivity κ is advantageous for increasing the dimensionless figure of merit ZT. ZT=S 2 σT / κ (1)
[0045] On the other hand, the thermal conductivity κ is expressed as the sum of the carrier thermal conductivity κcar and the lattice thermal conductivity κlat, as shown in the following formula (2). The carrier thermal conductivity κcar is expressed as formula (3), known as the Wiedemann-Franz law. Here, L is the Lorentz number, which can be treated as a constant for metal materials, but it is known that in semiconductor materials it is smaller than the constant used for metal materials, and according to Applied Physics Letters, (US), 2015, Vol.3, 041506, it is proposed to define L as shown in formula (4). S in formula (4) is the Seebeck coefficient. κ=κcar+κlat (2) κcar=LσT (3) L=1.5+exp(-│S│ / 116) (4)
[0046] Thus, when the carrier thermal conductivity κcar is low, the electrical conductivity σ also tends to be low, and a low carrier thermal conductivity κcar is not necessarily advantageous in terms of increasing the dimensionless figure of merit ZT. On the other hand, the lattice thermal conductivity κlat is not directly proportional to the electrical conductivity σ, and a low lattice thermal conductivity κlat is advantageous in terms of increasing the dimensionless figure of merit ZT.
[0047] The following sulfides may be used for purposes other than thermoelectric conversion materials. h-a M i-b Sn j-c D a+b+c S k Here, M is at least one element selected from Al, In, and Zn, and contains Zn. In addition, D is a metal element other than Cu, Al, In, Zn, and Sn. This sulfide satisfies a≧0, b≧0, c≧0, 0≦a+b+c≦0.2, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2. In addition, k is a value that maintains the electrical neutrality of the sulfide.
[0048] In this sulfide, D is, for example, at least one selected from the group consisting of Mn, Fe, Co, and Ni. D may be Ga.
[0049] This sulfide can be used, for example, as a material for energy conversion. For example, this sulfide may be used as a material for solar cells. In this case, the sulfide may be in the form of particles, film, or fiber. By including Zn, the band gap of the sulfide tends to be narrow. In addition, the ionic radius of Zn and the ionic radius of Cu are close to each other, and they are easily substituted, so that when the material is used as a material for solar cells, the properties of the material can be easily adjusted.
[0050] The following sulfides may be used for purposes other than thermoelectric conversion materials. h-a Al x-b1 In i-x-b2 Sn j-c Z a+b1+b2+c S k where Z is a metal element other than Cu, Al, In, and Sn. The sulfide satisfies 0≦x≦i, a≧0, b1≧0, b2≧0, c≧0, 0≦a+b1+b2+c≦0.5, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2. In addition, k is a value that maintains the electrical neutrality of the sulfide.
[0051] In this sulfide, Z is, for example, at least one element selected from the group consisting of Mn, Fe, Co, Ni, Zn, and Ga.
[0052] The following sulfides may be used for purposes other than thermoelectric conversion materials. h-a Al x-b3 Zinc i-x-b4 Sn j-c T a+b3+b4+c S kwhere T is a metal element other than Cu, Al, Zn, and Sn. The sulfide satisfies 0≦x≦i, a≧0, b3≧0, b4≧0, c≧0, 0≦a+b3+b4+c≦0.2, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2. In addition, k is a value that maintains the electrical neutrality of the sulfide.
[0053] In this sulfide, T is, for example, at least one element selected from the group consisting of Mn, Fe, Co, Ni, and Ga.
[0054] The following sulfides may be used for purposes other than thermoelectric conversion materials. h-a R i-b Sn j-c E a+b+c S k Here, R is at least one element selected from Al, In, Zn, and Ga, and includes Ga. In addition, E is a metal element other than Cu, Al, In, Zn, Ga, and Sn. This sulfide satisfies a≧0, b≧0, c≧0, 0≦a+b+c≦0.2, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2. In addition, k is a value that maintains the electrical neutrality of the sulfide.
[0055] E is, for example, at least one element selected from the group consisting of Mn, Fe, Co, and Ni.
[0056] The following sulfides may be used for purposes other than thermoelectric conversion materials. h-a Al x-b1 Ga i-x-b2 Sn j-c J a+b1+b2+c S k Here, J is a metal element other than Cu, Al, Ga, and Sn. The sulfide satisfies 0≦x≦i, a≧0, b1≧0, b2≧0, c≧0, 0≦a+b1+b2+c≦0.5, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2. In addition, k is a value that maintains the electrical neutrality of the sulfide.
[0057] J is, for example, at least one element selected from the group consisting of Mn, Fe, Co, Ni, and Zn.
[0058] The above sulfides contained in the thermoelectric conversion material and the above sulfides usable for applications other than thermoelectric conversion materials can be synthesized, for example, by a liquid phase reduction method. Sulfide particles of nanometer order (for example, having a particle diameter of 100 nm or less) synthesized by the liquid phase reduction method are expected to efficiently scatter phonons and exhibit low lattice thermal conductivity by adjusting the particle diameter. The sulfide particles have an average particle diameter of, for example, 100 nm or less. The sulfide particles desirably have an average particle diameter of 50 nm or less. The average particle diameter of the sulfide particles can be determined, for example, as follows. Ten or more sulfide particles are observed by TEM to determine the particle diameter of each particle. At this time, a rectangle with the minimum area circumscribing the TEM image of each particle is drawn, and the lengths of the long side and the short side of the drawn rectangle are defined as the long axis and the short axis of the particle, respectively, and the particle diameter of each particle is determined from the relationship of particle diameter = (long axis of particle + short axis of particle) / 2. Then, the arithmetic mean of the particle sizes of each particle is determined as the average particle size of the sulfide particles.
[0059] An example of the liquid phase reduction method will be described. A mixed liquid containing a copper compound, a tin compound, at least one of an aluminum compound, a zinc compound, an indium compound, and a gallium compound, and a sulfur compound and / or elemental sulfur is prepared in a predetermined organic solvent. The mixed liquid is prepared, for example, in an environment at room temperature and normal pressure. Next, the mixed liquid is placed in an environment filled with an inert gas and at a temperature of 150 to 350°C for a predetermined period of time to synthesize a thermoelectric conversion material.
[0060] In this method, the copper compounds are, for example, (i) CuCl and CuCl 2 (ii) Cu(NO 3 ) 2 (iii) Cu(CH 3 COO), Cu(CH 3 COO) 2, and copper carboxylates such as copper neodecanoate, or (iv) complex compounds such as copper acetylacetonate that are soluble in organic solvents. In this method, the tin compound is, for example, SnCl 2 and SnCl 4 The aluminum compound, zinc compound, indium compound, and gallium compound are, for example, chlorides of aluminum, zinc, indium, and gallium, nitrates of aluminum, zinc, indium, and gallium, carboxylates of aluminum, zinc, indium, and gallium, or complex compounds of aluminum, zinc, indium, and gallium, such as acetylacetonate. The sulfur compound in this method is, for example, (i) thiols such as octanethiol, decanethiol, and dodecanethiol, (ii) dithiols such as octanedithiol, decanedithiol, and dodecanedithiol, (iii) thiourea, or (iv) organic sulfur compounds such as thioacetamide. The organic sulfur compound is preferably a liquid organic sulfur compound such as thiol. In this case, the liquid organic sulfur compound can play the role of an organic solvent in the mixed solution. The mixed solution may contain a liquid organic compound other than the liquid organic sulfur compound. Such liquid organic compounds may include, for example, (i) amines, such as oleylamine; (ii) unsaturated fatty acids, such as myristoleic acid, palmitoleic acid, and oleic acid; or (iii) polyhydric alcohols, such as ethylene glycol, triethylene glycol, and tetraethylene glycol.
[0061] The inert gas used in this method is not particularly limited as long as it is inert to the mixed liquid, and examples of the inert gas include rare gases such as argon, and nitrogen. The pressure in the environment in which the mixed liquid is placed is preferably normal pressure.
[0062] In this method, the period during which the environment filled with inert gas and maintained at a temperature of 150 to 350° C. is maintained is, for example, 1 to 5 hours.
[0063] According to this method, the synthesized sulfide is precipitated. The precipitated sulfide is separated by a solid-liquid separation method such as centrifugation using a predetermined organic solvent, and is washed with a predetermined organic solvent and dried as necessary. In this way, a thermoelectric conversion material containing the sulfide can be obtained.
[0064] The thermoelectric conversion material thus obtained may be in a powder form. The thermoelectric conversion material may be produced by further sintering the powder containing sulfide. The method for sintering the powder containing sulfide is not particularly limited, but may be, for example, spark plasma sintering or hot pressing. The sintering temperature is, for example, 150°C to 1500°C, and preferably 200°C to 1000°C. The sintering time is, for example, 0 to 10 minutes, and preferably 0 to 5 minutes. The temperature rise time required from the start of the sintering process to reach the maximum temperature during the sintering process is, for example, 2 to 10 minutes. For example, the temperature inside the die filled with the powder is raised to the maximum temperature within the above-mentioned temperature rise time, and the temperature inside the die is kept at the maximum temperature for a predetermined time (sintering time), and then the heating is stopped and the sintered body is allowed to cool naturally. In the sintering by spark plasma sintering, the pressure for pressing the powder during the sintering process is, for example, 0.5 MPa to 100 MPa, and preferably 5 MPa to 50 MPa. On the other hand, in the case of sintering by hot pressing, the pressure applied to the powder during the sintering step is, for example, 5 MPa to 500 MPa, preferably 200 MPa to 400 MPa. When the pellet size is large or when the mechanical strength of the pellet needs to be increased, it is preferable to further extend the sintering time or the temperature rise time in order to obtain a uniform sintered body. This sintering step can be carried out in an inert gas atmosphere or a vacuum atmosphere. This sintering step is preferably carried out in a vacuum atmosphere.
[0065] The sulfides contained in the thermoelectric conversion material and the sulfides usable for applications other than thermoelectric conversion materials may be produced by, for example, sintering a powder obtained by mixing copper powder, tin powder, and at least one of aluminum powder, zinc powder, indium powder, and gallium powder. A known device such as a ball mill can be used to mix these powders. The method for sintering the powder is, for example, spark plasma sintering or hot pressing. In this case, the conditions for the spark plasma sintering or hot pressing described above regarding the spark plasma sintering or hot pressing for the powder containing the sulfide obtained by the liquid phase reduction method can be applied as the conditions for the spark plasma sintering or hot pressing.
[0066] Each of the above sulfides contained in the thermoelectric conversion material and the above sulfides usable for applications other than as thermoelectric conversion materials may be synthesized by a melting method or a hydrothermal synthesis method.
[0067] The melting method is a method of reacting raw materials at high temperature to obtain a target compound. One example of the melting method is a method in which raw materials are vacuum-sealed in a quartz tube or the like so as to have a mass ratio of the target materials, and the raw materials are reacted at a predetermined reaction temperature using a heating device such as an electric furnace.
[0068] An example of the hydrothermal synthesis method will be described. A mixture is prepared by adding and mixing at least one of a copper compound, a tin compound, an aluminum compound, a zinc compound, an indium compound, and a gallium compound, and a sulfur compound or elemental sulfur in water so as to obtain a desired material ratio. Next, the mixture is placed in an environment of a temperature of 150 to 300°C and a pressure of 0.5 to 9 MPa (megapascals) for a predetermined period of time to perform hydrothermal synthesis. The copper compound in this manufacturing method is, for example, CuCl and CuCl 2 Chlorides such as Cu(NO 3 ) 2 Copper nitrate such as Cu(CH 3 COO) and Cu(CH 3 COO) 2 The tin compound in this manufacturing method is, for example, SnCl 2and SnCl 4 The aluminum compound, zinc compound, indium compound, and gallium compound in this manufacturing method are, for example, aluminum chloride, zinc chloride, indium chloride, and gallium chloride, aluminum nitrate, zinc nitrate, indium nitrate, and gallium nitrate, or aluminum carboxylate, zinc carboxylate, indium carboxylate, and gallium carboxylate. The sulfur compound in this manufacturing method is, for example, an organic sulfur compound such as thiourea and thioacetamide.
[0069] <Thermoelectric conversion element> The above-mentioned sulfide-containing thermoelectric conversion material for thermoelectric conversion materials can be used to fabricate a thermoelectric conversion element. In this case, the thermoelectric conversion element includes the above-mentioned sulfide-containing thermoelectric conversion material.
[0070] For example, the thermoelectric conversion element includes a thermoelectric conversion material containing the above-mentioned sulfide and a conductor connected to the thermoelectric conversion material. As shown in FIG. 1A, the thermoelectric conversion element 1 includes, for example, a plurality of first thermoelectric conversion materials 10, a plurality of second thermoelectric conversion materials 20 arranged alternately with the first thermoelectric conversion materials 10, and a conductor 30 connecting the adjacent first thermoelectric conversion materials 10 and the second thermoelectric conversion materials 20. For example, the plurality of first thermoelectric conversion materials 10 and the plurality of second thermoelectric conversion materials 20 are connected in series by the conductor 30. The first thermoelectric conversion material 10 is a thermoelectric conversion material containing the above-mentioned sulfide. On the other hand, the second thermoelectric conversion material 20 is a known n-type semiconductor that can be used in a thermoelectric conversion element. As shown in FIG. 1A, the conductor 30 is arranged on, for example, a predetermined substrate 40a or substrate 40b. Each of the substrates 40a and 40b is, for example, a ceramic substrate having high thermal conductivity.
[0071] As shown in FIG. 1B, the thermoelectric conversion element 2 includes, for example, a plurality of first thermoelectric conversion materials 50 and a conductor 60 that connects adjacent first thermoelectric conversion materials 50 to each other. For example, the plurality of first thermoelectric conversion materials 50 are connected in series by the conductor 60. The first thermoelectric conversion material 50 is a thermoelectric conversion material containing the above-mentioned sulfide. As shown in FIG. 1B, the conductor 60 is disposed, for example, on a predetermined substrate 70a or substrate 70b. Each of the substrate 70a and the substrate 70b is, for example, a ceramic substrate having high thermal conductivity. EXAMPLES
[0072] The present invention will be described in more detail below using examples. Note that the following examples are merely examples of the present invention, and the present invention is not limited to the following examples.
[0073] <Example 1> 3 millimoles (mmol) of copper acetate, 1 mmol of aluminum acetylacetone, 1 mmol of tin acetate, 100 ml of dodecanethiol, and 100 ml of oleylamine were mixed and stirred to obtain a uniformly dispersed mixed solution A. Next, a container containing mixed solution A was placed in a space filled with argon gas, and mixed solution A was heated to 260°C and stirred for 1 hour to obtain a liquid in which particles were precipitated. Methanol was added to the liquid thus obtained, and the mixture was centrifuged at 5000 rpm for 5 minutes to collect the precipitate. The collected precipitate was washed with hexane and methanol, and the solid containing the precipitate was vacuum-dried using a vacuum dryer. In this way, the powder according to Example 1 was obtained.
[0074] The powder according to Example 1 was sintered using a spark plasma sintering apparatus (manufactured by Sinterland, model number: LABOX-125). This sintering was carried out by filling a die with 0.75 g of the powder according to Example 1, raising the temperature inside the die to 450° C. at a rate of 100° C. / min, and then maintaining the temperature inside the die at 450° C. for 2 minutes. Thereafter, both sides of the pellet, which is the sintered product taken out from inside the die, were polished using polishing paper with a grain size of #2000 based on the Japanese Industrial Standards (JIS) R 6001:1998, to obtain a sample according to Example 1.
[0075] <Example 2> 18 mmol of copper neodecanoate, 6 mmol of indium 2-ethylhexanoate, 6 mmol of tin 2-ethylhexanoate, 100 ml of dodecanethiol, and 100 ml of oleylamine were mixed and stirred to obtain a uniformly dispersed mixed liquid B. Next, a container containing mixed liquid B was placed in a space filled with nitrogen gas, and mixed liquid B was heated to 240°C and stirred for 3 hours to obtain a liquid in which particles were precipitated. Methanol was added to the liquid thus obtained, and the mixture was centrifuged at 5000 rpm for 5 minutes to collect the precipitate. The collected precipitate was washed with hexane and methanol, and the solid containing the precipitate was vacuum-dried using a vacuum dryer. In this way, a powder according to Example 2 was obtained. The powder according to Example 2 was sintered and polished in the same manner as the powder according to Example 1 to obtain a sample according to Example 2.
[0076] <Example 3> 5 mmol of copper acetate, 0.75 mmol of aluminum acetylacetone, 0.25 mmol of zinc acetylacetone, 2 mmol of tin acetate, 100 ml of dodecanethiol, and 100 ml of oleylamine were mixed and stirred to obtain a uniformly dispersed mixture C. The mixture C thus obtained was subjected to the same processes as in Example 1 to prepare a powder, sinter and polish it, to obtain a sample according to Example 3.
[0077] <Example 4> 5 mmol of copper acetate, 0.5 mmol of aluminum acetylacetone, 0.5 mmol of zinc acetylacetone, 2 mmol of tin acetate, 100 ml of dodecanethiol, and 100 ml of oleylamine were mixed and stirred to obtain a uniformly dispersed mixture D. The mixture D thus obtained was subjected to the same powder preparation, sintering, and polishing treatment as in Example 1 to obtain a sample according to Example 4.
[0078] <Example 5> 5 mmol of copper acetate, 0.25 mmol of aluminum acetylacetone, 0.75 mmol of zinc acetylacetone, 2 mmol of tin acetate, 100 ml of dodecanethiol, and 100 ml of oleylamine were mixed and stirred to obtain a uniformly dispersed mixture E. The mixture E thus obtained was subjected to the same powder preparation, sintering, and polishing treatment as in Example 1 to obtain a sample according to Example 5.
[0079] <Example 6> 5 mmol of copper acetate, 1 mmol of zinc acetylacetone, 2 mmol of tin acetate, 100 ml of dodecanethiol, and 100 ml of oleylamine were mixed and stirred to obtain a uniformly dispersed mixture F. The mixture F thus obtained was subjected to the same powder recovery, sintering, and polishing treatment as in Example 1 to obtain a sample according to Example 6.
[0080] <Example 7> 5 mmol of copper acetate, 0.75 mmol of aluminum acetylacetone, 0.5 mmol of gallium acetylacetone, 2 mmol of tin acetate, 100 ml of dodecanethiol, and 100 ml of oleylamine were mixed and stirred to obtain a uniformly dispersed mixed solution G. Next, a container containing mixed solution G was placed in a space filled with argon gas, and mixed solution G was heated to 260°C and stirred for 1 hour to obtain a liquid in which particles were precipitated. The liquid thus obtained was centrifuged at 5000 rpm for 5 minutes to collect the precipitate. The collected precipitate was washed with hexane, and the solid containing the precipitate was vacuum-dried using a vacuum dryer. In this way, a powder according to Example 7 was obtained. The powder according to Example 7 was sintered and polished in the same manner as the powder according to Example 1 to obtain a sample according to Example 7.
[0081] <Example 8> 5 mmol of copper acetate, 0.5 mmol of aluminum acetylacetone, 1 mmol of gallium acetylacetone, 2 mmol of tin acetate, 100 ml of dodecanethiol, and 100 ml of oleylamine were mixed and stirred to obtain a uniformly dispersed mixture H. The mixture H thus obtained was subjected to the powder recovery, sintering, and polishing treatment in the same manner as in Example 7 to obtain a sample according to Example 8.
[0082] <Example 9> 5 mmol of copper acetate, 0.25 mmol of aluminum acetylacetone, 1.5 mmol of gallium acetylacetone, 2 mmol of tin acetate, 100 ml of dodecanethiol, and 100 ml of oleylamine were mixed and stirred to obtain a uniformly dispersed mixture I. The mixture I thus obtained was subjected to the same powder recovery, sintering, and polishing treatment as in Example 7 to obtain a sample according to Example 9.
[0083] <Example 10> 5 mmol of copper acetate, 2 mmol of gallium acetylacetonate, 2 mmol of tin acetate, 100 ml of dodecanethiol, and 100 ml of oleylamine were mixed and stirred to obtain a uniformly dispersed mixed solution J. The thus obtained mixed solution J was subjected to powder recovery, sintering, and polishing treatments in the same manner as in Example 7 to obtain a sample according to Example 10.
[0084] <X-ray Diffraction Measurement> Using an X-ray diffractometer (manufactured by Rigaku Corporation, product name: MiniFlex600), X-ray diffraction patterns of each powder before sintering by the discharge plasma sintering according to Examples 1 and 2 were obtained. CuKα rays were used as the X-rays. The X-ray diffraction patterns of the powders according to Examples 1 to 6 are shown in FIGS. 2A to 2F. From this result, it was suggested that the powder before sintering by the discharge plasma sintering according to Example 1 had a crystal structure of the wurtzite type. Also, the powder before sintering by the discharge plasma sintering according to Example 2 had a crystal structure of the wurtzite type and was suggested to have a composition of Cu 3 InSnS 5 . The powders before sintering by the discharge plasma sintering according to Examples 3 to 10 had a crystal structure of the wurtzite type and had compositions of Cu 3 Al 0.75 Zn 0.25 SnS 5 , Cu 3 Al 0.5 Zn 0.5 SnS 5 , Cu 3 Al 0.25 Zn 0.75 SnS 5 , Cu 3 ZnSnS 5 , Cu 3 Al 0.75 Ga 0.25 SnS 5 , Cu 3 Al 0.5 Ga 0.5 SnS 5 , Cu 3 Al 0.25 Ga 0.75 SnS 5 , and Cu 3 GaSnS 5 respectively.
[0085] Using an energy dispersive X-ray analyzer (EDS) (Hitachi High-Technologies Corporation, product name: TM3030), EDS was performed on the samples made from the powders before sintering by spark plasma sintering in Examples 1 and 3 to 10 and the samples made from each sample after sintering by spark plasma sintering in Examples 1 and 3 to 6, and the abundance ratios of Cu, Al, Zn, Ga, and Sn based on the atomic number were measured. The results are shown in Table 1.
[0086] [Table 1]
[0087] An X-ray diffraction pattern was obtained for each sample after sintering by spark plasma sintering according to Examples 1 to 8 using an X-ray diffractometer (manufactured by Rigaku Corporation, product name: MiniFlex600) or a fully automated multipurpose X-ray diffractometer (manufactured by Rigaku Corporation, product name: SmartLab). CuKα rays were used as X-rays. The X-ray diffraction patterns for each sample after sintering by spark plasma sintering according to Examples 1 to 8 are shown in Figures 3A to 3H. These results suggest that each sample after sintering by spark plasma sintering according to Examples 1 to 8 has at least one of a wurtzite crystal structure and a zinc blende crystal structure.
[0088] <Measurement of thermal conductivity> The thermal conductivity of each sample according to Examples 1 to 8 was measured at a plurality of temperatures in the range of 300 to 700 K. The thermal conductivity was measured using a laser flash method thermal property measurement device (manufactured by Netzsch, product name: Lfa457) or a laser flash method thermal property measurement device (manufactured by Kyoto Electronics Manufacturing Co., Ltd., product name: LFA-502). The results are shown in Figures 4A to 4H.
[0089] <Measurement of Electrical Conductivity and Seebeck Coefficient> Using a thermoelectric property evaluation device (manufactured by ULVAC-RIKO, product name: ZEM-3) or a thermoelectric property evaluation device (manufactured by Ozawa Scientific Co., product name: RZ2001i), the electrical conductivity σ of each sample according to Examples 1 to 8 was measured at a plurality of temperatures in the range of 300 to 700K. The results are shown in FIGS. 5A to 5H. In addition, the resistivity ρ was obtained by taking the reciprocal of the electrical conductivity σ of each sample according to Examples 1 and 2. The results are shown in FIGS. 5A and 5B. Using the above thermoelectric property evaluation device, the Seebeck coefficient S of each sample according to Examples 1 to 8 was measured. The results are shown in FIGS. 6A to 6H. In each sample according to Examples 1 to 8, the power factor PF was obtained based on the following formula (5) from the Seebeck coefficient S and the electrical conductivity σ. The results are shown in FIGS. 6A to 6H. PF = S 2 σ (5)
[0090] <Determination of Carrier Thermal Conductivity and Lattice Thermal Conductivity> From the measurement results of the Seebeck coefficient S for each sample according to Examples 1 to 8, the Lorenz number L was determined using the above formula (4). From the determined Lorenz number L and the measurement results of the electrical conductivity σ, the carrier thermal conductivity κcar at the measurement temperature of the thermal conductivity of each sample according to Examples 1 to 8 was calculated using the above formula (3). The lattice thermal conductivity κlat at the measurement temperature of the thermal conductivity of each sample according to Examples 1 to 8 was determined by subtracting the carrier thermal conductivity κcar from the thermal conductivity according to formula (2). The results are shown in FIGS. 4A to 4H. As shown in FIGS. 4A and 4B, each sample according to Examples 1 and 2 had a lattice thermal conductivity of 1.3 W / (m·K) or less at 373 to 673K. Each sample according to Examples 3 to 8 had a lattice thermal conductivity of 0.7 W / (m·K) or less at 373 to 673K.
[0091] <Dimensionless Performance Index> From the results shown in FIGS. 4A to 6H, the dimensionless performance index ZT for each sample according to the examples was determined according to formula (1). The results are shown in FIGS. 7A to 7H.
[0092] <TEM Observation> Samples for TEM observation were prepared from the powders before sintering according to Examples 1, 3 to 10, and TEM observation was performed. TEM photographs of the powders before sintering according to Examples 1, 3 to 10 are shown in Figures 8A to 8I. In the TEM photographs of each sample, 10 or more particles were selected, a rectangle with the minimum area circumscribing the TEM image of each particle was drawn, and the lengths of the long side and short side of the drawn rectangle were determined as the long axis and short axis of the particle, respectively. The lengths of the long side and short side of the drawn rectangle were determined as the long axis and short axis of the particle, respectively, and the particle size of each particle was determined from the relationship of particle size = (particle long axis + particle short axis) / 2. The arithmetic mean of the particle size of each particle was then determined as the average particle size. Table 2 shows the average values of the long axis and short axis of the powders in each Example and the average particle size.
[0093] [Table 2]
Claims
1. Cu h-a M i-b Sn j-c D a+b+c S k A sulfide having a composition represented by the formula: M is at least one element selected from Al, In, and Zn; D is Ga; a ≧ 0, b ≧ 0, c ≧ 0, 2.8 ≦ h ≦ 3.2, 0.8 ≦ i ≦ 1.2, and 0.8 ≦ j ≦ 1.2 are satisfied, and k is a value that maintains the electrical neutrality of the sulfide, When M contains Zn, 0≦a+b+c≦0.2; When M does not contain Zn, it contains sulfides, where 0≦a+b+c≦0.5; The sulfide has at least one of a wurtzite crystal structure and a zinc blende crystal structure. Thermoelectric conversion materials.
2. The sulfide is Cu h-a A x-b1 In i-x-b2 Sn j-c A a+b1+b2+c S k The composition is represented by A is Ga; 0≦x≦i, a≧0, b1≧0, b2≧0, c≧0, 0≦a + b1 + b2 + c≦0.5, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2 are satisfied, and k is a value that maintains the electrical neutrality of the sulfide. The thermoelectric conversion material according to claim 1 .
3. The sulfide is Cu h-a A x-b3 Zinc i-x-b4 Sn j-c Q a+b3+b4+c S k The composition is represented by Q is Ga; 0≦x≦i, a≧0, b3≧0, b4≧0, c≧0, 0≦a + b3 + b4 + c≦0.2, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2 are satisfied, and k is a value that maintains the electrical neutrality of the sulfide. The thermoelectric conversion material according to claim 1 .
4. Cu h-a A x-b1 In i-x-b2 Sn j-c Z a+b1+b2+c S k A sulfide having a composition represented by the formula: Z is Zn or Ga; Contains a sulfide that satisfies 0≦x≦i, a≧0, b1≧0, b2≧0, c≧0, 0≦a+b1+b2+c≦0.5, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2, and k is a value that maintains the electrical neutrality of the sulfide; The sulfide has at least one of a wurtzite crystal structure and a zinc blende crystal structure. Thermoelectric conversion materials.
5. Cu h-a A x-b3 Zinc i-x-b4 Sn j-c T a+b3+b4+c S k A sulfide having a composition represented by the formula: T is Ga; Contains a sulfide that satisfies 0≦x≦i, a≧0, b3≧0, b4≧0, c≧0, 0≦a+b3+b4+c≦0.2, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2, and k is a value that maintains the electrical neutrality of the sulfide; The sulfide has at least one of a wurtzite crystal structure and a zinc blende crystal structure. Thermoelectric conversion materials.
6. Cu h-a R i-b Sn j-c E a+b+c S k A sulfide having a composition represented by the formula: R is at least one element selected from Al, In, Zn, and Ga; E is a metal element other than Cu, Al, In, Zn, Ga, and Sn; a ≧ 0, b ≧ 0, c ≧ 0, 2.8 ≦ h ≦ 3.2, 0.8 ≦ i ≦ 1.2, and 0.8 ≦ j ≦ 1.2 are satisfied, and k is a value that maintains the electrical neutrality of the sulfide, Contains sulfides, where a+b+c=0; The sulfide has at least one of a wurtzite crystal structure and a zinc blende crystal structure. Thermoelectric conversion materials.
7. Cu h-a A x-b1 G i-x-b2 Sn j-c J a+b1+b2+c S k A sulfide having a composition represented by the formula: J is a metal element other than Cu, Al, Ga, and Sn; Contains a sulfide that satisfies 0≦x≦i, a≧0, b1≧0, b2≧0, c≧0, a+b1+b2+c=0, 2.8≦h≦3.2, 0.8≦i≦1.2, and 0.8≦j≦1.2, and k is a value that maintains the electrical neutrality of the sulfide; The sulfide has at least one of a wurtzite crystal structure and a zinc blende crystal structure. Thermoelectric conversion materials.
8. The thermoelectric conversion material according to any one of claims 1 to 7, wherein the sulfide is sintered.
9. A thermoelectric conversion element comprising the thermoelectric conversion material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Thermoelectric conversion material
JP2016048730A
Thermoelectric Apparatus And Applications Thereof
US20130312806A1
Thermoelectric conversion material, thermoelectric conversion element, powder for thermoelectric conversion material, and method for producing thermoelectric conversion material
WO2017203938A1